Vs30 and depth to bedrock estimates from integrating HVSR measurements and geology-slope approach in the Oslo area, Norway - Ghione, Federica; Köhler, Andreas; Dichiarante, Anna Maria; Aarnes, Ingrid; Oye, Volker (Frontiers in Earth Science, 2023)
In order to estimate well-constrained seismic hazard and risk on local scales, the knowledge of site amplification factors is one of several important requirements. Seismic hazard studies on national or regional scales generally provide the level of earthquake shaking only at bedrock conditions, thereby avoiding the difficulties that are caused through local site effects. Oftentimes, local site conditions are not well understood or even non-existent. In this study we investigate an efficient and non-invasive methodology to derive the local average shear wave velocity in the uppermost 30 meters of the ground (Vs30). The Vs30 value is a useful parameter to define soil classes and soil amplification used in seismic hazard assessment and to extend the knowledge of the site to include the depth to basement rock. At the level of the municipality of Oslo, there is currently no map available that describes the Vs30, and as such any seismic risk study is lacking potentially critical information on local site amplification. The new proposed methodology includes the use of existing well databases (with knowledge on minimum basement depth), topographic slope derived from Digital Elevation Models (as a proxy for both depth to basement and Vs30, integrated with geological maps) and near-surface Quaternary geological maps. The Horizontal to Vertical Spectral Ratio (HVSR) method and a statistics-based geological mapping tool (COHIBA) are used to integrate the various sources of data estimates. Finally, we demonstrate our new methodology and workflow with data from three different regions within the Oslo municipality and propose an approach to conduct cost-efficient mapping for seismic site amplification on a general municipality scale.